Face Transplants: An International History. (28th June 2021) - Alberti, Fay Bound; Hoyle, Victoria
: Face transplants have attracted global media and public attention since the 1990s. The first recipient, Isabelle Dinoire, found herself at the centre of a dramatic episode of surgical innovation after her transplant was announced in November 2005. Subsequently 47 transplants have been conducted worldwide (including two retransplants) up to August 2020, and these have been accompanied by extensive news coverage. Hundreds of papers on the medical, physical, psychological, and ethical implications of the procedure have been published in the scientific literature, disproportionate to the incidence of the procedure. Face transplants have also featured in films, television, and fiction, indicating an appetite for interrogating the social and interpersonal implications of facial difference. However, the history of facial transplantation has largely been unexplored. This article provides the first international history of the global development and implementation of facial transplantation. Using published medical literature, media coverage, and oral history interviews with key participants as source material, it situates the experimental transplant in national, institutional, and professional contexts. It argues that charting the history of face transplants over a 30 year period from initial discussions in 1991 to the present provides a valuable case study through which to consider surgical cultures and discourses of medical innovation in the twenty-first century.